Anatomical and histochemical features of the arsenic hyperaccumulator Pteris vittata (Pteridaceae). Issue 1 (2nd January 2022) - Li, Linbao; Li, Teng; Wu, Di; Wu, Jinhua; Zhang, Mengdi; Zhang, Xia; He, Xin; Zheng, Hai; Yang, Chaodong; Huang, Guiyun; Zhou, Cunyu
ABSTRACT: The perennial fern Pteris vittata (Pteridaceae) is an arsenic hyperaccumulator and a phytoremediator of contaminated soils. In this study, we investigated the anatomical and histochemical features, as well as the permeability of the P. vittata roots, in order to identify the characters that allow this species to thrive in xeromorphic rocky environments and to hyperaccumulate ions. The primary structures of the P. vittata sporophyte include a suberized endodermis, lignified sclerenchyma layers, bifacial mesophyll, and a thick cuticle, all of which reflected an adaption to xeromorphic rocky environments. The pectin-rich surfaces of the rhizodermis and the root hairs were underlain by a lignified cortex, and permeability tests using a berberine tracer showed that these structures retained large volumes of berberine, consistent with ion hyperaccumulation. Thus, the anatomical and histochemical features of P. vittata identified in this study were consistent with adaptations to xeromorphic environments and the ability to hyperaccumulate ions.